COORDONATA PRAXIOLOGICĂ A FORMĂRII CULTURII ECONOMICE ÎN FAMILIE - Anastasia OLOIERU (Moldova State University, 2020)
În articol este abordată familia din punct de vedere economic. Este conturată importanța formării economice a copiilor în cadrul familiei. Nevoia de cultură economică este investigată în cadrul unui experiment pedagogic. Sunt descriși factorii care facilitează formarea culturii economice în familie.   PRAXIOLOGICAL COORDINATION OF THE FORMATION OF ECONOMIC CULTURE IN FAMILY The article deals with the family from an economic point of view. The importance of children's economic formation within the family is outlined. The need for economic culture is being investigated in a pedagogical experiment. The factors that facilitate the formation of the economic culture in the family are described.